The Black Industrialist Programme’s prospects to the advancement of developmental state in South Africa - Mlondi Vilakazi; Candice Moore (Africa’s Public Service Delivery & Performance Review, 2023)
Background: South Africa has made considerable progress in terms of economic development since the dawn of democracy in 1994. However, the pace and distribution of that progress have not been equitably reflected across all demographics, especially between black and white people. With a decline of manufacturing, the ‘developmental state’ has featured as a strong theme to try and reignite industrialisation in the country. Under this framework, one of the policies driven by the South African government is the Black Industrialist Programme, which aims to increase the manufacturing output while empowering black people.